Sensing Inflammation Biomarkers with Electrolyte‐Gated Organic Electronic Transistors. Issue 20 (22nd August 2021) - Burtscher, Bernhard; Manco Urbina, Pamela Allison; Diacci, Chiara; Borghi, Simone; Pinti, Marcello; Cossarizza, Andrea; Salvarani, Carlo; Berggren, Magnus; Biscarini, Fabio; Simon, Daniel T.; Bortolotti, Carlo A.
Abstract: An overview of cytokine biosensing is provided, with a focus on the opportunities provided by organic electronic platforms for monitoring these inflammation biomarkers which manifest at ultralow concentration levels in physiopathological conditions. Specifically, two of the field's state‐of‐the‐art technologies—organic electrochemical transistors (OECTs) and electrolyte gated organic field effect transistors (EGOFETs)—and their use in sensing cytokines and other proteins associated with inflammation are a particular focus. The overview will include an introduction to current clinical and "gold standard" quantification techniques and their limitations in terms of cost, time, and required infrastructure. A critical review of recent progress with OECT‐ and EGOFET‐based protein biosensors is presented, alongside a discussion onthe future of these technologies in the years and decades ahead. This is especially timely as the world grapples with limited healthcare diagnostics during the Coronavirus disease (COVID‐19)pandemic where one of the worst‐case scenarios for patients is the "cytokine storm." Clearly, low‐cost point‐of‐care technologies provided by OECTs and EGOFETs can ease the global burden on healthcare systems and support professionals by providing unprecedented wealth of data that can help to monitor disease progression in real time. Abstract : The roles, significance, and potential diagnostic capabilities of cytokines, the body's endogenous inflammation biomarkers are introduced. The report proceeds with a focus on cytokine biosensors based on organic electrochemical transistors and electrolyte gated organic field effect transistors and concludes with an outlook on the benefits of such organic electronic technologies.